2006
DOI: 10.1080/08880010600812561
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy of the Femur

Abstract: Melanotic neuroectodermal tumor of infancy (MNTI) is a rare neoplasm that often occurs during the first year of life. More than 90% of MNTIs occur in the head and neck region, with most on the anterior part of the maxillary ridge. MNTI has also been reported in the mediastinum, thigh, foot, shoulder, and gonads. Here the authors report a rare case of MNTI of the femur in a 3-month-old child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…7 Infants typically present with a rapidly growing, painless, nonulcerative mass affecting the maxilla or other craniofacial structures, 4 destroying adjacent bone and causing esthetic deformities and feeding disruption. The mass is typically firm, with smooth swelling and bluish-black coloration.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Infants typically present with a rapidly growing, painless, nonulcerative mass affecting the maxilla or other craniofacial structures, 4 destroying adjacent bone and causing esthetic deformities and feeding disruption. The mass is typically firm, with smooth swelling and bluish-black coloration.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…This yielded a total of 69 publications, which included the 116 cases (Supplementary Table 1). 4,7,[12][13][14][15][16] In addition, data were collected on 356 additional cases that were reported in the literature from 1918 through 2004 from 3 major systematic reviews. 18,81,82 These cases were combined with the 116 cases published from January 2005 through December 2013 (Supplementary Table 1) to constitute a total of 472 cases for analysis.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Rare, non-head and neck sites include epididymis, [5][6][7] testis, 8,9 ovaries, 10 and soft tissue and bones of the extremities. [11][12][13][14] The largest retrospective study 2 that reviewed 472 reported cases within the literature showed mainly maxillary involvement in 279 cases (62.2%), followed by the skull (70; 15%), mandible (35; 7%), male reproductive system (23; 5%), central nervous system (20; 4%), soft tissue (7; 1%), and female reproductive system (3; ,1%). They also determined that the median age of diagnosis was 5 months.…”
mentioning
confidence: 99%
“…В большинстве случаев МНЭО локализуется в области головы и шеи, однако описаны случаи локализации процесса в центральной нервной системе (ЦНС), мягких тканях, яичке, придатке яичка, средостении, бедренной кости и т. д. [3][4][5]. Исторически для описания МНЭО использовались различные синонимы, такие как пигментная амелобластома, опухоль сетчатки, меланотическая эпителиальная одонтома.…”
Section: Introductionunclassified